USING CAT TOOLS IN FREELANCE TRANSLATION: INSIGHTS FROM A CASE STUDY, BY PAULINA PIETRZAK & MICHAL KORNACKI - Albuquerque, Alexandra (POLISSEMA – Revista de Letras do ISCAP, 2022)
Pietrzak, P., & Kornacki, M. (2021). Using CAT Tools in Freelance Translation: Insights from a Case Study (1st ed.). Routledge.